Efficient Privacy-Preserving Data Sanitization over Cloud Using Optimal GSA Algorithm. (13th July 2018) - Renuga, S; Jagatheeshwari, S S K
Abstract: Data sharing is one of the important tasks in cloud computing application. When large volume of data is stored in the cloud, there is a chance for malicious attacks on the sensitive information stored in the cloud due to traditional poor privacy-preserving methods in the cloud. In this paper, an efficient data transform in the cloud with privacy-preserving method using sanitization algorithm is proposed. The optimal key is chosen here to process the sanitization algorithm effectively and gravitational search algorithm (GSA) is used to select the optimal key. The optimal key value is difficult to predict while using GSA algorithm. So this work is more secure compared to the existing privacy-preserving approach. The performance of the proposed technique is compared with artificial bee colony algorithm (ABC), elliptic curve cryptography (ECC), and RSA (Rivest–Shamir–Adleman). From the experimental result, this proposed method serves more secure with minimum execution time and hiding failure, maximum dissimilarity value when compared to the existing method. Finally, the result obtained shows that the proposed system has improved the privacy performance in cloud computing. The implementation will be done in JAVA using cloud simulator.